1978
DOI: 10.1017/s0305000900002105
|View full text |Cite
|
Sign up to set email alerts
|

Who, why, when, and how: a development study

Abstract: Fifty children between the ages of 3; 0 and 5; 6 were asked six types of wh- questions following videotaped sequences. It is argued that differential difficulty of various forms of who questions supports a parallel model of information retrieval and processing during discourse. The differential difficulty of why and when questions are, however, attributable to a necessary progression in the ability to encode the relevant concepts linguistically. Responses to how questions are difficult because they involve a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 2 publications
0
26
0
Order By: Relevance
“…Secan, Egel and Tilley (1989) suggested that "Why" questions may be difficult to grasp because of the absence of any visible referent. However, developmental studies suggest that a large improvement in the understanding of "Why" questions occurs betweentheages ofthree and four (Cairns &Hsu, 1977). There areno studies directly relevant to adults with mild to moderate intellectual disability on the understanding of "Why" questions.…”
Section: Discussionmentioning
confidence: 99%
“…Secan, Egel and Tilley (1989) suggested that "Why" questions may be difficult to grasp because of the absence of any visible referent. However, developmental studies suggest that a large improvement in the understanding of "Why" questions occurs betweentheages ofthree and four (Cairns &Hsu, 1977). There areno studies directly relevant to adults with mild to moderate intellectual disability on the understanding of "Why" questions.…”
Section: Discussionmentioning
confidence: 99%
“…In studying children's responses to wh-questions, Cairns & Hsu (1978) found that for why, when, and how questions, a simple count of the number of correct responses does not adequately reflect the child's performance. They found that among the correct and incorrect responses, there are degrees of correctness and incorrectness which could be categorized into four developmentally sequenced response types: (1) totally uncomprehending or 'I don't know' response; (2) a response indicating some understanding but a failure to form more than a minimal, fixed, or ritualized response; (3) a response indicating understanding but the response is slightly semantically or syntactically incorrect ; and (4) a completely correct, contextually accurate response.…”
mentioning
confidence: 99%
“…For later acquired wh-words (why, when, how) which represent the abstract constructs of cause-effect, time, and manner respectively, SES differences were pronounced, with middle-SES children comprehending significantly more of these types of questions than the low-SES children. Earlier studies of whquestion comprehension indicate that children's abilities to comprehend whDownloaded from 122 words are developmentally sequenced with those wh-words representing concrete referents acquired first and those representing abstract referents later (Cairns & Hsu 1978, Ervin-Tripp 1970, Tyack & Ingram 1977. Further, research on SES differences in language use indicates that middle-SES children use language more than low-SES children to analyse and to reason about past or present experiences, to project beyond present experiences to future events, and to talk about alternative courses and subsequent consequences (Bernstein 1962, Blank, Rose & Berlin 1978, Tough 1977.…”
mentioning
confidence: 99%
“…words are developmentally sequenced with those wh-words representing concrete referents acquired first and those representing abstract referents later (Cairns & Hsu 1978, Ervin-Tripp 1970, Tyack & Ingram 1977. Further, research on SES differences in language use indicates that middle-SES children use language more than low-SES children to analyse and to reason about past or present experiences, to project beyond present experiences to future events, and to talk about alternative courses and subsequent consequences (Bernstein 1962, Blank, Rose & Berlin 1978, Tough 1977.…”
mentioning
confidence: 99%